2019
DOI: 10.7717/peerj.6259
|View full text |Cite
|
Sign up to set email alerts
|

Blood parasites in Passeriformes in central Germany: prevalence and lineage diversity of Haemosporida (Haemoproteus,PlasmodiumandLeucocytozoon) in six common songbirds

Abstract: BackgroundAvian Haemosporida are vector-borne parasites that commonly infect Passeriformes. Molecular analyses revealed a high number of different lineages and lineage specific traits like prevalence and host-specificity, but knowledge of parasite prevalence and lineage diversity in wild birds in Central Germany is still lacking.ResultsBlood samples from a total of 238 adult and 122 nestling songbirds belonging to six species were investigated for infections with avian haemosporidian genera and lineages (Haemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 75 publications
2
11
0
Order By: Relevance
“…In addition to methodology results, this study contributes to the knowledge of the prevalence of Haemoproteus, Plasmodium, Leucocytozoon, Lankesterella and Trypanosoma species and microfilariae of filariid nematodes in common European birds (Additional file 1: Table S1). The obtained data corroborate with previous studies that reported prevalence of these blood parasites [66][67][68][69]. In the present study, Haemoproteus species had the highest prevalence (Additional file 1: Table S1).…”
Section: Discussionsupporting
confidence: 92%
“…In addition to methodology results, this study contributes to the knowledge of the prevalence of Haemoproteus, Plasmodium, Leucocytozoon, Lankesterella and Trypanosoma species and microfilariae of filariid nematodes in common European birds (Additional file 1: Table S1). The obtained data corroborate with previous studies that reported prevalence of these blood parasites [66][67][68][69]. In the present study, Haemoproteus species had the highest prevalence (Additional file 1: Table S1).…”
Section: Discussionsupporting
confidence: 92%
“…Haemosporidians occur worldwide except in Antarctica (Beadell et al, 2009) and most infections are relatively benign, probably due to long-term host parasites evolutionary associations (Bennet et al, 1993). The occurrence of these protozoa has been reported from several birds’ species (Schmid et al, 2017; Dimitrov et al, 2018; Ferreira-Junior et al, 2018; Valkiunas et al, 2019; Schumm et al, 2019) and from dipteran species (Ionică et al, 2017; Žiegytė et al, 2017; Martin et al, 2019; Schoener et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Avian haemosporidian parasites ( Plasmodium , Haemoproteus, Leucocytozoon and Fallisia ) are widespread and remarkably diverse; this diversity frequently exceeds that of avian hosts [15]. During the past ten years, it has been shown that several Haemoproteus species can be harmful to their avian hosts, compromising their health and even causing mortality, especially in non-adapted birds [69].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have addressed parasite diversity and the phylogenetic relationships of haemosporidian parasites of various avian hosts [4, 5, 1318], but information about vector competence and patterns of sporogonic development of these pathogens remains insufficient. Haemoproteus ( Parahaemoproteus ) species (Haemosporida: Haemoproteidae) are cosmopolitan in countries with warm and temperate climates [2, 3].…”
Section: Introductionmentioning
confidence: 99%